Animal size and sea water temperature, but not pH, influence a repeatable startle response behaviour in a wide-ranging marine mollusc. (March 2021) - Clements, Jeff C.; Ramesh, Kirti; Nysveen, Jacob; Dupont, Sam; Jutfelt, Fredrik
Abstract : Startle response behaviours are important in predator avoidance and escape for a wide array of animals. For many marine invertebrates, however, startle response behaviours are understudied, and the effects of global change stressors on these responses are unknown. We exposed two size classes of blue mussels ( Mytilus edulis  ×  trossulus ) to different combinations of temperature (15 and 19 °C) and pH (8.2 and 7.5 pHT ) for 3 months and subsequently measured individual time to open following a tactile predator cue (i.e. startle response time) over a series of four consecutive trials. Time to open was highly repeatable in the short term and decreased linearly across the four trials. Individuals from the larger size class had a shorter time to open than their smaller-sized counterparts. High temperature increased time to open compared to low temperature, while pH had no effect. These results suggest that bivalve time to open is repeatable, related to relative vulnerability to predation and affected by temperature. Given that increased closure times impact feeding and respiration, the effect of temperature on closure duration may play a role in the sensitivity to ocean warming in this species and contribute to ecosystem level effects. Highlights: We measured startle response (time to open) in mussels following a predator cue. We tested effects of temperature, pH and size and measured repeatability. Larger mussels opened faster; repeatable startle response; evidence of habituation. High temperature increased time to open; no effect of pH. Blue mussels are sensitive to temperature and vulnerable to climate change.